2022
DOI: 10.1128/mra.00719-22
|View full text |Cite
|
Sign up to set email alerts
|

Coding-Complete Genome Sequence of an African Swine Fever Virus from an Outbreak in 2021 among Domestic Pigs in Pangasinan, Philippines

Abstract: We report a coding-complete genome sequence of an African swine fever virus from an outbreak in 2021 among domestic pigs in Pangasinan, Philippines using Oxford Nanopore Technologies minION. The linear genome assembly is a single contig with 192,377 bp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…African swine fever (ASF) is a lethal disease of pigs emerging globally and is gaining momentum in Asia since its introduction to China in August 2018 1 , followed by several countries in Southeast Asia [2][3][4][5][6] . ASF virus (ASFV), a large double-stranded DNA virus and a member of the Asfarviridae family, is the causative agent.…”
Section: Intradermal Needle-free Injection Prevents African Swine Fev...mentioning
confidence: 99%
“…African swine fever (ASF) is a lethal disease of pigs emerging globally and is gaining momentum in Asia since its introduction to China in August 2018 1 , followed by several countries in Southeast Asia [2][3][4][5][6] . ASF virus (ASFV), a large double-stranded DNA virus and a member of the Asfarviridae family, is the causative agent.…”
Section: Intradermal Needle-free Injection Prevents African Swine Fev...mentioning
confidence: 99%
“…Spatiotemporal patterns of ASF in the Philippines based on 2019–2022 data revealed that ASF outbreaks are lowest during the hot and dry months, with possible explanations on virus sensitivity to temperature and infrequent pig movements between farms and administrative borders [ 21 ]. Assuming the presence of unreported outbreaks in the study sites, the low seroprevalence could also be explained by the high mortality rates caused by the pathogenic ASFV (genotype II) present in the Philippines [ 19 , 20 ], meaning those remaining pigs that survived from ASF or were exposed to the virus were likely sold or delivered to the abattoir. The level of ASF seropositivity among pigs for slaughter in this study is comparable to the neighboring Southeast Asian country of Cambodia, showing a low ASF seroprevalence (2.6%) in pigs for slaughter in Phnom Penh.…”
Section: Discussionmentioning
confidence: 99%
“…Another study also revealed that the ASFV circulating in some affected areas of Central Luzon showed 100% sequence similarity with sequences reported from India, Malaysia, and Vietnam [ 42 ]. Recently, the coding-complete genome sequence of ASFV, a single contig with 192,377 bp isolated from an outbreak in 2021 and locally sequenced using Nanopore sequencing technology, was first reported and showed that the local isolate belongs to the same clade as ASFV strains from Timor-Leste, China, Ukraine, Belgium, and Poland [ 43 ]. These sequence data came from the blood samples of pigs from ASF outbreaks in two different provinces.…”
Section: Asf Epidemiology and Surveillancementioning
confidence: 99%